ANALYSIS ON PRADHAN MANTRI KAUSHAL YOJANA: WITH SPECIAL REFERENCE TO JHANSI - Ekta (International Journal of Advanced Science and Technology, 2020)
Pradhana Mantri Kaushal VikasYojana (PMKVY) is the lead result based fitness getting ready arrangement of the new Service of Expertise Improvement and Enterprise (MSDE). This inclination affirmation and reward plot hopes to engage and initiate a broad number of Indian youth to take up expertise planning and wrap up clearly employable and win their occupation. NDA government, centering towards skilling up the poor Indian and towards advancing business enterprise among them, presented Pradhan Mantri Kaushal Vikash Yojana. PMKVY is a skill confirmation plot with the accept that it will help an enormous number of Indian youth to take up industry-pertinent skill training that will help them in verifying better Livelihood opportunities. Under the arrangement, cash related reward would be given to understudies who are viably arranged, assessed and guaranteed in expertise courses continue running by joined forces getting ready providers. This will bolster the productivity of the country’s workforce by enabling them to acquire incredible ability getting ready over an extent of sections. It will in like manner understand an adjustment in standpoint from input-based to result based ability planning in the country. This Research Study is study is an attempt for understanding the opinions of the Indian Youth in reference to PMKVY with special reference to Jhansi city.